Use of the arabic language in the children’s journalism in Algeria survey research : Journalistic types in ghomaida magazine - دليلة قدور; فاتح قدور (International Journal of Social Communication, 2023)
This research aimes to know the use of the arabic language in the children’s journalism in Algeria,through revealing faults record in the journalistc types of the magazine. The study used survey methodology and content analysis tool which allowed us to analyse nine numbers from the first number to the last number sinse march 2019 until juin year 2022. The study has achieved a lot of results :the percentage of linguistic errors reached 45,45%, and grammatical errors their percentage 36,36%, syntax faults 13,63%, also dictated faults 4,5%.